Wartości i postawy w emocjonalnych narracjach medialnych. Analiza zawartości przekazów mediów mainstreamowych w okresie pierwszej fali SARS-CoV-2 - Szegda, Joanna (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2020)
The aim of this article is to address the two following research questions: 1. What visual narratives about values and attitudes are constructed and imposed by mainstream media in different countries on their Instagram channels during the COVID pandemic; and 2. Whether narratives about values are dependent on the emotions encoded in the message. In order to verify the hypotheses, the authors analyse the content of 515 visual messages published on Instagram by dailies representing different countries. The research results allowed for the following conclusions: 1. The attitudes and values presented in media messages concerning the pandemic are determined by the current epidemiological situation and they are evoked to make the recipients feel more familiarized with the pandemic situation, get comforted but sometimes also scared or warned; 2. The set of values and attitudes differ depending on the particular emotion that prevails in a particular narrative; 3. The set of values appearing in the narratives of various national media globally is universal in nature.